2017
DOI: 10.1186/s13287-017-0599-x
|View full text |Cite
|
Sign up to set email alerts
|

Bone mesenchymal stem cells ameliorate ischemia/reperfusion-induced damage in renal epithelial cells via microRNA-223

Abstract: BackgroundRecent studies have indicated that microRNA-223 (miR-223) plays a role in the tissue-protective effect of mesenchymal stem cells (MSCs). NLR family-pyrin domain containing 3 (NLRP3) was reported to affect a renal ischemia/reperfusion (I/R) injury by exerting a direct effect on the renal tubular epithelium. Therefore, we investigated how miR-223 and NLRP3 might function in kidneys exposed to conditions of ischemia and subsequent reperfusion.MethodsHypoxia/reoxygenation (H/R) murine renal tubular epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…The mechanism regulating cell apoptosis is one of the most important aspects of renal protection. Indeed, the anti-apoptotic pathway has been reported in many studies with MSC-EVs treatment in a variety of rodent renal injury models, including AKI induced by I/R [24,31,33,104,106,[116][117][118]120,124,125], cisplatin [48,119,126], gentamicin [105], and glycerol [17], hypoxia-induced renal injury [60], aldosterone-induced renal injury [52], and UUO-induced CKD model [109]. Recent advances have gradually uncovered the specific miRNAs, their targets and signaling pathways involved in the effect of anti-apoptosis (Table 2), including PTEN, AKT, mTOR, dynamin-related protein 1 (DRP1), Sema3A, and ERK signaling pathway.…”
Section: Renal Protectionmentioning
confidence: 99%
“…The mechanism regulating cell apoptosis is one of the most important aspects of renal protection. Indeed, the anti-apoptotic pathway has been reported in many studies with MSC-EVs treatment in a variety of rodent renal injury models, including AKI induced by I/R [24,31,33,104,106,[116][117][118]120,124,125], cisplatin [48,119,126], gentamicin [105], and glycerol [17], hypoxia-induced renal injury [60], aldosterone-induced renal injury [52], and UUO-induced CKD model [109]. Recent advances have gradually uncovered the specific miRNAs, their targets and signaling pathways involved in the effect of anti-apoptosis (Table 2), including PTEN, AKT, mTOR, dynamin-related protein 1 (DRP1), Sema3A, and ERK signaling pathway.…”
Section: Renal Protectionmentioning
confidence: 99%
“…Several studies have shown that MSCs can attenuate collagen-induced arthritis, coxsackievirus B3-induced myocarditis, or ischemia/reperfusion (I/R)-induced renal injury by inhibiting NLRP3 inflammasome activation [ [12] , [13] , [14] ]. However, whether AMSC-Exo-based therapy can ameliorate ALF and modulate NLRP3 inflammasome is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In AKI mice models induced by ischemia-reperfusion injury, Bruno et al (27) found that MSC-EVs induced the expression of anti-apoptotic genes (Bcl-XL, Bcl2, and BIRC8) in renal tubular epithelial cells while simultaneously down-regulating pro-apoptotic genes (Casp1, Casp8, and LTA), thus reducing tubular cell apoptosis and conferring an anti-apoptotic phenotype necessary for tissue repair. Interestingly, the anti-apoptosis effect of MSC-EVs may be mediated in part by the transfer of miRNAs (miR-223 and miR-199a-3p) to tubular cells (54,55). In addition, MSC-EVs can directly shuttle several pro-angiogenesis transcription factors including vascular endothelial growth factor (VEGF) (52), insulin-like growth factor 1 (IGF-1) (56), and basic fibroblast growth factor (bFGF) (57) to the damaged renal tubular epithelial cells and enhance angiogenesis, which is considered as an important step in tissue regeneration.…”
Section: Msc-evs and Sepsis-induced Actue Kidney Injurymentioning
confidence: 99%